ANALYSIS OF MELODIES AND TEXTS IN KATONENG-KATONENG BY SEVEN PERKOLONG-KOLONG IN KARO DISTRICT - Naima Serenia Girsang; Mauly Purba; Vanesia Amelia Sebayang; Pulumun P. Ginting; Ikhwanuddin Nasution (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2026)
This research examines the Katoneng-katoneng vocal tradition in Karo society, specifically focusing on the Pemasu-masun (blessing) segment. The primary aim is to analyze the musical characteristics, textual meanings, and the transmission process of this tradition through seven prominent perkolong-kolong (traditionalsingers) across different generations. The study addresses the shift from traditional instrumentation to electronic keyboards and the potential loss of melodic authenticity and depth of meaning due to declining interest among the younger generation. The study employs a qualitative method with an ethnomusicologicalapproach. The theoretical framework integrates Bruno Nettl’s Musical Character Theory to analyze melodic structures, Ferdinand de Saussure’s Semiotics to decode textual signs, and Robert Sibarani’s Oral Tradition Theory to examine performance and local wisdom. Data were gathered through field observations, in-depthinterviews, audio-visual documentation, and prescriptive musical transcriptions to map the stylistic variations of each informant.The findings reveal that the musical characteristics of Pemasu-masun follow a cyclical structure: pattern A (antecedent), which tends to use the Aeolian mode, and pattern B (consequent),which aligns with the Phrygian mode. Aesthetic variations are defined by the perkolong-kolong’s improvisational skill in executing vocal ornaments known as rengget. Textually, the Pemasu-masun lyrics serve as a system of signs representing the philosophical value of teneng (tranquility) and the Rakut Si Telu kinshipstructure. The transmission process occurs orally through observation and social interaction. In conclusion, despite the transformation of musical accompaniment, the perkolong-kolong remains a vital guardian of cultural identity, ensuring the continuity of Karo’s traditional values amidst modernization.  Keywords: Katoneng-katoneng, Pemasu-masun, Perkolong-kolong, Semiotics.